The making of a Christian aristocracy : social and religious change in the western Roman Empire - Salzman, Michele Renee (Harvard University Press, 2002)
"What did it take to cause the Roman aristocracy to turn to Christianity, changing centuries-old beliefs and religious traditions? Michele Salzman takes a fresh approach to this much-debated question. Focusing on the lives of over four hundred aristocratic men and women as well as on writings and archeological evidence, she brings new understanding to the process by which pagan aristocrats became Christian, and Christianity became aristocratic." "Examining the world of the ruling class - its institutions and resources, its values and style of life - Salzman paints a fascinating picture, especially of aristocratic women. Her study yields new insight into the religious revolution that transformed the late Roman Empire."--Jacket